An urban-rural comparison of the prevalence, patterns and factors associated with elder abuse in Oyo State, southwestern Nigeria. (2014)
Background; The social restructuring of families due to modernization and urbanization has led to a decrease in the available primary care givers for the elderly and places them in a position of risk of abuse. Elder abuse has hitherto been uncharacterized in Nigeria. This study compares the prevalence, patterns and factors associated with elder abuse in a rural and an urban community in Oyo State, south western Nigeria. Methods: A comparative cross sectional survey of the elderly (aged 60 years and above) was conducted in selected rural (Iwajowa) and urban (Ibadan South-East) Local Government Areas of Oyo State, Nigeria in 2010. Data were obtained using a semi-structured questionnaire and were analysed using Stata version 12. Results: Overall prevalence of abuse was 29.1%. Emotional abuse (15.8%) was the most frequent followed by financial abuse (14.3%) and physical abuse (9.0%). Only 2 (0.6%) respondents in the urban area reported sexual abuse. The urban and rural prevalence of abuse were: emotional abuse 23.7% versus 8.0%; physical abuse 14.5% versus 3.6% and financial abuse 20.9% versus 7.7% respectively. Although there were differences based on location, for the total population, predictors of elder abuse were, urban dwelling, being unmarried, and financially dependence. Conclus ion : This study has revealed that elder abuse is not uncommon in these communities. All forms of elder abuse are quite prevalent except sexual abuse. Financial insufficiency and dependence on family members for care are contributory factors. Appropriate social and welfare interventions are required to ameliorate the problem.